204k views
5 votes
Directions: Simplify by combining like terms in each of the following expressions.

1. 1s2 + 10s2 - 21st =


2. 5st - st - t2 =


3. x^{2} + x^{2} + x^{3} =


4. 6x - 4x + 2=


5. 9x - 3s - 2t=


6. 87x + 8x - 1 =


7. 3x + 6x - 2 =


8. 8s - 4s + 3s =


9. 12 + x - 11x =


10. 12x + 24x - 3x - 4 =


11. 14t + 8t - 12t =


12. 17g + 14g - 6g + g =


13. 13 + 12 - 12 + 13x =


14. 17s - 3s + 3s =


15. 14t - 12t + t =

PLEASE ANSWER AS SOON AS POSSIBLE

User Atomicus
by
7.5k points

1 Answer

3 votes

Answer:

Step-by-step explanation:iyghjyghuyjhmn

User Cameron Fredman
by
6.6k points